Solitary testicular metastasis post-prostatectomy for prostatic ductal adenocarcinoma: case report and literature review - Chang, Bo; Zhang, Manqing; Hou, Yifan; Li, Wenbin; Li, Song; Zhang, Jianhua; Wang, Chenyang; Zhang, Qiangqiang; Hou, Junqing (Frontiers in Oncology, 2025)
Background and PurposeProstatic ductal adenocarcinoma (PDA) constitutes a rare and notably aggressive histological subtype within the spectrum of prostate malignancies, distinguished by a heightened propensity for recurrence and metastasis compared to prostatic acinar adenocarcinoma (PAA). Testicular metastasis in PDA is exceptionally rare. Despite sporadic reports in the literature, a consensus regarding the optimal therapeutic approach remains elusive. This study retrospectively analyzes a singular case of PDA manifesting with solitary testicular metastasis after laparoscopic radical prostatectomy (LRP), consolidating insights into clinical, histopathological, molecular, and therapeutic aspects, alongside existing scholarly discourse.MethodsWe present the case of a 63-year-old gentleman diagnosed with pure PDA (pT3aN0, Gleason score 4 + 4 = 8), exhibiting a serum prostate-specific antigen (PSA) level exceeding 100 ng/ml. Subsequently, the patient underwent androgen deprivation therapy (ADT) followed by LRP. Subsequently, at 17 months post-LRP, local recurrence and a right testicular mass emerged, prompting pelvic radiotherapy and docetaxel chemotherapy. Ultimately, the patient underwent right orchiectomy 65 months post-LRP, with pathological findings confirming metastatic PDA. Four months post-orchiectomy, PSA levels declined to 1.77 ng/ml. Additionally, a comprehensive review of published literature concerning PDA complicated by testicular metastasis was conducted.ResultsThe patient derived therapeutic benefits from ADT, LRP, radiation therapy, and orchiectomy, resulting in objective symptom alleviation and a reduction in PSA. Nevertheless, docetaxel proved inefficacious. The literature review indicated variability in outcomes across diverse treatment modalities.ConclusionsProlonged surveillance is imperative for patients diagnosed with PDA. Urologists must remain vigilant regarding uncommon sites of metastasis, particularly in instances of elevated PSA.